Association between Helicobacter pylori infection and triglyceride levels: a nested cross-sectional study - Xie, Jun; Wang, Jinyun; Zeng, Rong; Xie, Yong (Frontiers in Endocrinology, 2023)
Background: Currently, the available evidence regarding the relationship between the lipid profile and Helicobacter pylori (H. pylori) infection is limited and conflicting.There is also a dearth of studies that have explored the possibility of sex-specific differences in the association between H. pylori infection and triglyceride levels.: We conducted a cross-sectional study involving 1,146 participants utilizing data from the National Health and Nutrition Examination Survey (NHANES) 1999-2000 conducted in the United States. A logistic regression model was employed to evaluate the association between H. pylori seropositivity and triglyceride levels.Subgroup analyses stratified by sex were conducted to explore sex-specific differences in this association.Results: Serum triglyceride levels were significantly higher in H. pylori-seropositive participants than in H. pylori-seronegative participants. In the logistic regression analysis, there was a positive correlation between H. pylori seropositivity and triglyceride levels (OR=1.231; 95% CI, 1.016-1.491; P=0.033). In the subgroup analysis, the adjusted association between serum triglycerides and H. pylori seropositivity was significant in females (OR=1.732; 95% CI, 1.113-2.696; P=0.015) but not in males (OR=1.091; 95% CI, 0.698-1.705; P=0.704).The association between high triglyceride levels and H. pylori infection is specific to the female population.